Pragmatic Forces in the Language of Two American Presidential Candidates - Shilva Lioni (English Department, Faculty of Humanities, Andalas University, 2018)
This article explains about pragmatic force that found in the language of two American presidential candidates in 2012 US Presidential Debate about foreign policy where the purpose on sharing a belief and influencing the other’s people view are appeared significantly in the utterances of two candidates. The pragmatic forces in this research are revealed by analyzing the illocutionary force that appeared and the reason of its performing related to the context of the utterance through pragmatics’ perspective, speech act. The result of analysis indicates that (i) four of five types of illocutionary forces were found and (ii) two of three reasons are used by the two American presidential candidates on the debate. The paper tries to highlight the pragmatic force that the speakers want to deliver where on this case was focused on sharing their belief in order to influence the other people’s (society and audiences) view. The paper also highlights some of the general considerations relating to the contexts of utterances. In analyzing the text, the writer used a combination method of quantitative and qualitative.